A Legend of Reading Abbey - MacFarlane, Charles, 1799-1858 (Salt Lake City, UT : Project Gutenberg, 2013)
"A Legend of Reading Abbey" by Charles MacFarlane is a historical fiction novel written in the mid-19th century. Set during the 12th century in England, it tells of the turbulent times surrounding King Stephen's reign and the conflicts arising from the struggle for the throne between Stephen and Matilda, the disinherited daughter of King Henry I. The narrative is presented through the eyes of a Benedictine monk named Felix, who recounts events surrounding the Reading Abbey, touching on themes of faith, loyalty, and the chaos of medieval politics. The opening of the novel introduces the abbey and the political landscape of England during a time of civil strife. It describes the construction of Reading Abbey and the privileges it holds, such as exemption from various taxes and tributes. Felix, a youthful novice at the abbey, observes the community's efforts to celebrate solemn occasions even as they face imminent danger. The chapter sets into motion the arrival of a mysterious infant left at the abbey's gates, leading to intrigue among the monks and foreshadowing the turmoil that ensues as the nation descends into conflict, particularly as news of mounting battles and a civil war reaches their ears. (This is an automatically generated summary.)
Release date is 2013-01-08
E-text prepared by sp1nd, Mary Meehan, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (http://archive.org)
Keywords: Great Britain -- History -- Stephen, 1135-1154 -- Fiction